Glucose: an energy currency and structural precursor in articular cartilage and bone with emerging roles as an extracellular signaling molecule and metabolic regulator - Mobasheri, Ali (Frontiers, 2012)
In the skeletal system glucose serves as an essential source of energy for the development, growth, and maintenance of bone and articular cartilage. It is particularly needed for skeletal morphogenesis during embryonic growth and fetal development. Glucose is vital for osteogenesis and chondrogenesis, and is used as a precursor for the synthesis of glycosaminoglycans, glycoproteins, and glycolipids. Glucose sensors are present in tissues and organs that carry out bulk glucose fluxes (i.e., intestine, kidney, and liver). The beta cells of the pancreatic islets of Langerhans respond to changes in blood glucose concentration by varying the rate of insulin synthesis and secretion. Neuronal cells in the hypothalamus are also capable of sensing extracellular glucose. Glucosensing neurons use glucose as a signaling molecule to alter their action potential frequency in response to variations in ambient glucose levels. Skeletal muscle and adipose tissue can respond to changes in circulating glucose but much less is known about glucosensing in bone and cartilage. Recent research suggests that bone cells can influence (and be influenced by) systemic glucose metabolism. This focused review article discusses what we know about glucose transport and metabolism in bone and cartilage and highlights recent studies that have linked glucose metabolism, insulin signaling, and osteocalcin activity in bone. These new findings in bone cells raise important questions about nutrient sensing, uptake, storage and processing mechanisms and how they might contribute to overall energy homeostasis in health and disease. The role of glucose in modulating anabolic and catabolic gene expression in normal and osteoarthritic chondrocytes is also discussed. In summary, cartilage and bone cells are sensitive to extracellular glucose and adjust their gene expression and metabolism in response to varying extracellular glucose concentrations.